The influence of the upper echelons in the return on the assets of companies that make up part of the non-cyclical consumer goods and services economic sector - Daiane Antonini Bortoluzzi; Maryely Andrea Jimenez Franco; Silvio Aparecido Silva Aparecido Silva; Rogério João Lunkes (AD-minister, 2017)
The upper echelons theory, which was initially introduced by Hambrick and Mason (1984), affirms that the cognitions, values, and perceptions of senior executives influence the strategy selection process, and consequently, the company’s performance. Accordingly, the overall objective of this study was to verify the existence of the influence of demographic characteristics of senior executives in the business economic performance of the companies listed in the non-cyclical sector of the BM&FBOVESPA (Sao Paulo Stock Exchange in Brazil) in 2014. The study sample consists of 39 companies of the non-cyclical sector and the data collected were then provided by 182 directors. Based on the results, it was noted that among variables such as education level, age, gender, and time in office, age was the only variable that did not show any statistically significant relationship with the organizational performance.